Overview of the Role of Epicollect5: Extracting Data from Populations for Health Sectors - Daswito, Rinaldi; Ilmaskal, Radian (RRZ Scientific Publishing, 2024)
The demand for real-time, precise data in public health has driven the adoption of advanced tools like Epicollect5, a mobile and web-based application. Epicollect5 facilitates efficient data collection, management, and analysis, enabling healthcare professionals to address health challenges effectively. Integrating geospatial capabilities, offline functionality, and customizable survey tools supports diverse applications, including epidemiological studies, disease surveillance, and community health evaluations. Its open-source nature ensures accessibility in resource-limited settings, enhancing scalability and cost-effectiveness. However, challenges like limited technological access, data privacy concerns, and integration complexities persist. Epicollect5’s user-friendly interface, real-time data synchronization, and collaborative features have revolutionized health data management despite these hurdles. This editorial highlights its transformative role in public health, emphasizing its contributions to disease prevention and resource allocation. As digital health evolves, Epicollect5 exemplifies the potential of technology-driven solutions in shaping global health strategies.